Clinical evaluation of deep brain stimulation of nucleus accumbens/anterior limb of internal capsule for opioid relapse prevention: protocol of a multicentre, prospective and double-blinded study. Issue 2 (13th February 2019) - Qu, Liang; Ge, Shunnan; Li, Nan; Wang, Wei; Yang, Kaijun; Wu, Ping; Wang, Xuelian; Shi, Jie
Abstract : Introduction: Deep brain stimulation (DBS) is a new potential surgical treatment for opioid dependence. However, the implement of DBS treatment in addicted patients is currently controversial due to the significant associated risks. The aim of this study was mainly to investigate the therapeutic efficacy and safety of bilateral DBS of nucleus accumbens and the anterior limb of the internal capsule (NAc/ALIC-DBS) in patients with refractory opioid dependence (ROD). Methods and analysis: 60 patients with ROD will be enrolled in this multicentre, prospective, double-blinded study, and will be followed up for 25 weeks (6 months) after surgery. Patients with ROD (semisynthetic opioids) who meet the criteria for NAc/ALIC-DBS surgery will be allocated to either the early stimulation group or the late stimulation group (control group) based on the randomised ID number. The primary outcome was defined as the abstinence rate at 25 weeks after DBS stimulation on, which will be confirmed by an opiate urine tests. The secondary outcomes include changes in the Visual Analogue Scale (VAS) score for craving for opioid drugs, body weight, as well as psychological evaluation measured using the 17-item Hamilton Depression Rating Scale, the Hamilton Anxiety Rating Scale, the Pittsburgh Sleep Quality Index, Fagerstrom test for nicotine dependence assessment, social disability screening schedule, the Activity of Daily Living Scale, the 36-item Short Form-Health Survey and safety profiles of both groups. Ethics and dissemination: The study received ethical approval from the medical ethical committee of Tangdu Hospital, The Fourth Military Medical University, Xi'an, China. The results of this study will be published in a peer-reviewed journal and presented at international conferences. Trial registration number: NCT03424616 ; Pre-results.